Tribes in Bawean as "the Miniature of Indonesia" - Bea Anggraini, Sri Wiryanti Budi Utami, (Opción, 2019)
This study explores the unique cultural phenomena of the tribes in Bawean who identify themselves as Bawean people and interpret “the miniature of Indonesia” as their cultural identity. The ethnographic method through the “thick description” technique in this study enables the researchers to formulate the substance of a group of people’s consciousness who identify themselves as being Bawean. As a result, the tradition of wandering and Islamic beliefs has become a cohesive basis between Creole culture tribes. In conclusion, the tribes in Bawean who proud themselves as Bawean community, they are subversive to the idea of regional and language-based nationalism